What shapes a galaxy? – unraveling the role of mass, environment, and star formation in forming galactic structure. Issue 1 (5th February 2019) - Bluck, Asa F L; Bottrell, Connor; Teimoorinia, Hossen; Henriques, Bruno M B; Mendel, J Trevor; Ellison, Sara L; Thanjavur, Karun; Simard, Luc; Patton, David R; Conselice, Christopher J; Moreno, Jorge; Woo, Joanna
Abstract: We investigate the dependence of galaxy structure on a variety of galactic and environmental parameters for ∼500 000 galaxies at z < 0.2, taken from the Sloan Digital Sky Survey data release 7 (SDSS-DR7). We utilize bulge-to-total stellar mass ratio (B/T)* as the primary indicator of galactic structure, which circumvents issues of morphological dependence on waveband. We rank galaxy and environmental parameters in terms of how predictive they are of galaxy structure, using an artificial neural network approach. We find that distance from the star-forming main sequence (ΔSFR), followed by stellar mass ( M * ), are the most closely connected parameters to (B/T)*, and are significantly more predictive of galaxy structure than global star formation rate (SFR), or any environmental metric considered (for both central and satellite galaxies). Additionally, we make a detailed comparison to the Illustris hydrodynamical simulation and the LGalaxies semi-analytic model. In both simulations, we find a significant lack of bulge-dominated galaxies at a fixed stellar mass, compared to the SDSS. This result highlights a potentially serious problem in contemporary models of galaxy evolution.